Direct observations of the influence of solution composition on magnesite dissolution - King, H.; Putnis, Christine (2013)
In situ observations during atomic force microscopy experiments and ex situ observations after static and flow-through experiments were used to explore the effect of three different electrolytes on magnesite (MgCO3) dissolution at pH 2. The experiments showed that the magnesite dissolution rate varied in the order Cl->SO42">http://origin-ars.els-cdn.com/content/image/1-s2.0-S0016703713000641-si1.gif">NO3->Cl->SO42- when these anions were present in solution. Under the experimental conditions magnesite dissolution occurred via the removal of successive single surface layers, where changes in magnesite reactivity in the presence of different electrolytes could be observed as variations in the cycle length for the removal of one unit cell layer. The cycles began with the formation of sporadically distributed etch pits followed by the nucleation of homogeneously distributed etch pits. Coalescence of the etch pits formed isolated sections of the remnant surface, which then dissolved away. The timing of sporadic and homogeneous etch pit nucleation was constant despite the presence of different anions. However, the cycles in surface roughness and etch pit spreading rates indicate that the different anions affect step retreat rates and hence dissolution rates.Differences in magnesite reactivity can be attributed to the direct interaction of sulphate with the magnesite surface and the indirect effects of chloride and nitrate on the magnesite surface hydration and hydration of the Mg2+ ion in solution. In all experiments during the dissolution process evidence for the precipitation of a new phase was observed, either directly as precipitates forming on the magnesite surface in the AFM and after the experiments, seen in SEM analysis, or as changes in the Mg outlet concentration during flow-through experiments. EDX and Raman spectroscopy were used to analyse the composition of the precipitate and although it could not be definitively identified, considering previous observations the precipitate is most likely a hydrated Mg-carbonate phase with a MgCO3·xH2O composition. Thus, the formation of a precipitate can facilitate further magnesite dissolution by increasing the undersaturation of the interfacial solution.